2003
DOI: 10.1038/sj.bjc.6601211
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of cell death induced by the novel enzyme-prodrug combination, nitroreductase/CB1954, and identification of synergism with 5-fluorouracil

Abstract: Virus-directed enzyme prodrug therapy (VDEPT) utilising the bacterial enzyme nitroreductase delivered by a replication-defective adenovirus vector to activate the prodrug CB1954 is a promising strategy currently undergoing clinical trials in patients with a range of cancers. An understanding of the mechanism of tumour cell death induced by activated CB1954 will facilitate this clinical development. Here, we report that activated CB1954 kills cells predominantly by caspase-dependent apoptosis. This may have imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Other potential combined treatment modalities include specific targeting of the structurally abnormal tumour blood vessels with vascular targeting agents as we (Theys et al, 2001b) and others (Dang et al, 2001) have already successfully reported. In addition, more soluble derivatives of CB1954 that cause more effective tumour regression have recently been described (Wilson et al, 2002) and since 5-FU and CB1954 have been shown to act synergistically (Palmer et al, 2003), the combinatorial use of prodrug activating enzymes (CDase and NTR) might be a promising option for CDEPT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other potential combined treatment modalities include specific targeting of the structurally abnormal tumour blood vessels with vascular targeting agents as we (Theys et al, 2001b) and others (Dang et al, 2001) have already successfully reported. In addition, more soluble derivatives of CB1954 that cause more effective tumour regression have recently been described (Wilson et al, 2002) and since 5-FU and CB1954 have been shown to act synergistically (Palmer et al, 2003), the combinatorial use of prodrug activating enzymes (CDase and NTR) might be a promising option for CDEPT.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the nitroreductase (NTR) class of enzymes are of particular interest because their small size increases the likelihood of efficient clostridial expression. Nitroreductase converts the 4-nitrogroup of the prodrug CB1954 (5-aziridinyl-2,4-dinitrobenzamide) to its 10 000-fold more toxic 4-hydroxylamine (4HX) derivative, which can be further metabolised to form a DNA -DNA crosslinking and apoptosis-inducing agent (Palmer et al, 2003). Interestingly, both proliferating and nonproliferating cells, as they are often present in tumour areas with gradients of hypoxia, are killed (Cui et al, 1999).…”
mentioning
confidence: 99%
“…42,43 The prototype NTR prodrug CB 1954 (5-aziridinyl-2,4-dinitrobenzamide) is metabolized by NfsB to DNA reactive products that act as cell cycle independent cytotoxins 44 and which can provide a bystander effect as a result of diffusion from NTR-expressing cells. 45,46 Efficacy has been demonstrated in low density cell culture models [47][48][49][50][51][52] and against tumor xenografts using replication-defective viruses. [52][53][54][55] Phase I trials of CB 1954, alone 56 and in conjunction with a non-replicating NTR-armed adenovirus have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Double-positive cells are likely to represent late apoptotic cells that are no longer able to exclude PI. Palmer et al 57 suggested that mainly apoptotic cell death occurred in SKOV3 cells killed by NTR/ CB1954 and that this was dependent on caspase 8 and 9. Cell death after CB1954 application in NTR-recombinant transgenic mice was also reported to be apoptotic.…”
Section: Discussionmentioning
confidence: 99%